LEGAL IMPACT ON WAQF FOR PROPERTY DEVELOPMENT AND COMMERCIALISATION: COURT JUDGEMENTS ANALYSIS - Mohd Zakhiri Bin Md Nor; Alias Azahar; Ani Munirah Mohamad; Al Hanisham Mohd Khalid (Journal of Islamic, Social, Economics and Development, 2019)
There are 24000 hectares of waqf land not be fully developed in 2016 based on Waqf Foundation of Malaysia report. These waqf lands need to be developed for property development and commercialisation. However, there are many issues remained unsettled inter alia the interface between waqf and wasiat, the validity of waqf, the category of waqf land in particular leasehold and freehold of waqf land as well as the jurisdiction of the court to hear the case of waqf.It seems that all these issues may hamper the development and commercialisation of waqf land. Therefore, this paper shall analyse the administration of waqf land in Penang. This paper also shall examine the legal impact on waqf for property development and commercialisation through case analysis and court judgments. The methodology used in this paper is qualitative and content analysis method. This paper provides some suggestions and recommendations for better governance of waqf land particularly for property development and commercialisation